Evidence for Intraaxonal Spread of Listeria Monocytogenes from the Periphery to the Central Nervous System - Antal, Ellen‐Ann (Brain Pathol, 2006)
Rhombencephalitis due to Listeria monocytogenes is characterized by progressive cranial nerve palsies and subacute inflammation in the brain stem. In this paper, we report observations made on mice infected with L. monocytogenes. Unilateral inoculation of bacteria into facial muscle, or peripheral parts of a cranial nerve, induced clinical and histological signs of mainly ipsilateral rhombencephalitis. Similarly, unilateral inoculation of bacteria into lower leg muscle or peripheral parts of sciatic nerve was followed by lumbar myelitis. In these animals, intraaxonal bacteria were seen in the sciatic nerve and its corresponding nerve roots ipsilateral to the bacterial application site. Development of myelitis was prevented by transsection of the sciatic nerve proximally to the hindleg inoculation site. Altogether, our results support the hypothesis that Listeria rhombencephalitis is caused by intraaxonal bacterial spread from peripheral sites to the central nervous system.